Antioxidant and anti-elastase activity of Tampui (Baccaurea macrocarpa) and Ketapong (Terminalia badamia) barks and leaves - Ariani, Lusiana; Wulandari, Endah; Desmiaty, Yesi (Faculty of Pharmacy, Universitas Pancasila, 2024)
Elastase is a protease that is involved in the breakdown of elastin in the dermis. Likewise, free radicals can cause elastin damage. Inhibition of elastase enzyme activity and scavenging of free radicals can prevent premature aging of the skin, especially wrinkles. The current study was to investigate the antioxidant and elastase inhibition properties of the leaves and bark of the Tampui (Baccaurea macrocarpa L.) and Ketapong (Terminalia badamia L.) plants, which may be employed as an anti-aging ingredient in cosmetics and nutraceuticals. B. macrocarpa and T. badamia's leaves and bark were extracted using reflux and 96% ethanol. Anti-elastase was examined using N-succ-(Ala)3-nitroanilide as a substrate, and the DPPH reagent was used to test the antioxidants' activity. Phytochemical screening indicated the presence of flavonoids, quinone, tannins, and steroids. Antioxidant activity of B. macrocarpa leaves (BML), B. macrocarpa bark (BMB), T. badamia leaves (TBL), and T. badamia bark (TBB) had IC50 values were 15.09±0.51; 22.89±1.51; 36.43±1.94; 39.23±1.76 ppm, respectively. The anti-elastase activity of BML, BMB, TBL, and TBB had IC50 values were 48.86±2.29; 52.03±9.54; 44.42±4.53; 40.16±1.32 ppm, respectively. The ethanol extract of B. macrocarpa and T. badamia's leaves and bark exhibits anti-elastase and antioxidant action, proposing that it may be used as an anti-aging agent.